The fertility status of soils at rehabilitated degraded land in Universiti Putra Malaysia planted with pinus caribaea and Swietenia macrophylla - Abdul Malik, Mohammad Nazrin; Abdu, Arifin; Karam Singh, Daljit Singh; Jusop, Shamshuddin; Abdul Hamid, Hazandy; Jamaluddin, Aiza Shaliha; Basri, MohdHadi Akbar; Patek Mohd, Nur-Nazirah (Science Publications, 2015)
Soil fertility (both physical and chemical) is one of the important factors limiting plant growth. So, the fertility of the soils should be determined before growing crops and after the establishment of forest rehabilitation. A study was conducted to determine the fertility status of soils at rehabilitated degraded land in Universiti Putra Malaysia. The main objective was to compare the fertility of soils planted forest and pasture. Three sites studied were pines plantation (Pinus caribaea), mahogany plantation (Swietenia macrophylla) and pasture area. At each site, three squares of 20×20 m were selected and two depths of soil sample were collected, topsoil (0-20 cm) and subsoil (20-40 cm), from six points within the squares. The physical properties of the soils analyzed were bulk density, soil texture and moisture content, while the chemical properties were pH, total C and N, cation exchangeable capacity and exchangeable cations (Al, Ca, Mg, K and Na). The mean annual increment of height, diameter and volume of planted forest were also taken. The increment of height, diameter at breast height and volume of P. caribaea and S. macrophylla did not show any comparative difference for the cause of the similarity in the increment of patterns catalysed at the same location and climatic condition. P. caribaea showed higher SFI value compared to the other study plots, especially for the topsoil. In contrast, pasture plot had higher SEF, followed by P. caribaea and S. macrophylla plantation plots. P. caribaea showed the highest SFI value, while pasture plot had highest SEF, followed by P. caribaea and S. macrophylla plantation plots. Further study on bigger forest plantation having different types of plant species and land topography needs to be conducted to allow individuals and bodies in the field of forest plantation to gain the opportunity and implement the right approaches to establish forest plantation with good planting establishment practices.